2012
DOI: 10.1186/1471-2164-13-441
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic profiling of chicken adipose tissue in response to insulin neutralization and fasting

Abstract: BackgroundDomestic broiler chickens rapidly accumulate adipose tissue due to intensive genetic selection for rapid growth and are naturally hyperglycemic and insulin resistant, making them an attractive addition to the suite of rodent models used for studies of obesity and type 2 diabetes in humans. Furthermore, chicken adipose tissue is considered as poorly sensitive to insulin and lipolysis is under glucagon control. Excessive fat accumulation is also an economic and environmental concern for the broiler ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 62 publications
6
88
0
Order By: Relevance
“…Several recent studies have investigated the regulatory mechanisms of chicken adipogenesis using genome-wide analysis of mRNA (Ji et al 2012; Regassa and Kim 2015) and microRNA (Wang et al 2015). However, little is known about the regulatory mechanisms of adipogenesis.…”
mentioning
confidence: 99%
“…Several recent studies have investigated the regulatory mechanisms of chicken adipogenesis using genome-wide analysis of mRNA (Ji et al 2012; Regassa and Kim 2015) and microRNA (Wang et al 2015). However, little is known about the regulatory mechanisms of adipogenesis.…”
mentioning
confidence: 99%
“…Fatty acid esterification enhances TG synthesis and may be associated with increased content of muscle fat (Ji et al, 2012). Lysophosphatidic acid is further acylated at the sn-2 position by AGPAT to form phosphatidic acid (Bitou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, growth of the abdominal WAT in chickens is from a combination of adipose cell hyperplasia (increase in adipocyte number) and hypertrophy (increase in adipocyte volume) up to about 12 to 14 weeks, then it continues mainly by hypertrophy (Ji et al, 2012). The endocrine role of avian WAT remains enigmatic as many of the classical hormones found in mammalian adipose tissue have not been found in avians (Ramachandran et al, 2013).…”
Section: Endocrine Function Of Adipose Tissue and Its Implications Fomentioning
confidence: 99%
“…Relatively little is known about regulation of adipose tissue deposition and metabolism in chickens (Ji et al, 2012). Most studies have focused on broilers, and have shown that adipose tissue metabolism in the chicken is regulated by energy status and, to a lesser extent by insulin.…”
Section: Regulation Of Lipid Metabolism In the Laying Henmentioning
confidence: 99%